2016
DOI: 10.1111/ddi.12442
|View full text |Cite
|
Sign up to set email alerts
|

Inferring implications of climate change in south Florida hardwood hammocks through analysis of metacommunity structure

Abstract: Aim In order to explore how variation in regional biogeography would affect forest responses to climate change, we analysed metacommunity structure of trees in natural forest fragments across a boundary between tropical and subtropical temperature regimes. We wished to determine whether species assemblages were constrained by periodic cold temperatures, dispersal limitation and/ or local processes associated with fragment size, and consider how these influences might affect future species migration and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…Contrary to our first prediction, we did not find that subtropical northern Bahamas and Florida supported a depauperate (nested) subset of Caribbean SDTF diversity. This is in contrast to nested patterns found over smaller spatial extents in response to habitat fragmentation (Ross, Sah, Ruiz, Spitzig, & Subedi, ). While the Bahamian archipelago is geologically young and does not support high levels of seed plant endemism (Acevedo‐RodrĂ­guez & Strong, ), we found that SDTF composition in this northern subregion is distinct within the Caribbean Basin (Franklin et al., ), consistent with the climatic differences found there (Figure ; Fig.…”
Section: Discussioncontrasting
confidence: 88%
“…Contrary to our first prediction, we did not find that subtropical northern Bahamas and Florida supported a depauperate (nested) subset of Caribbean SDTF diversity. This is in contrast to nested patterns found over smaller spatial extents in response to habitat fragmentation (Ross, Sah, Ruiz, Spitzig, & Subedi, ). While the Bahamian archipelago is geologically young and does not support high levels of seed plant endemism (Acevedo‐RodrĂ­guez & Strong, ), we found that SDTF composition in this northern subregion is distinct within the Caribbean Basin (Franklin et al., ), consistent with the climatic differences found there (Figure ; Fig.…”
Section: Discussioncontrasting
confidence: 88%
“…In high‐resource sites such as in marsh hammocks, where moisture and nutrients are more abundant, trees exhibit traits that allow them to grow rapidly in height (high SLA and low wood specific gravity), supporting earlier observations describing early successional species (Ross et al. , Subedi et al. ).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, a wide distribution of few species (e.g., Bursera simaruba , Sideroxylon salicifolia, Eugenia foetida , E. axillaris ) across the whole region provides evidence of a nested metacommunity pattern (Ross et al. ), coupled with high intraspecific trait variation in these species (Appendix : Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ross et al. ). In their seed dispersal activities, birds and animals move easily across the whole forest exploiting most or all available habitat (Humphrey , Strong and Bancroft ).…”
Section: Discussionmentioning
confidence: 99%